Persuasion in Political TV. Interviews through Facial Movements - يحيى، سجى سالم; إبراهيم، أطياف حسن (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2023)
تستخدم طريقة الاتصال غير اللفظي من قبل المحاورين أثناء التحاور فهو جانب مهم في المحادثة والتفاعل اليومي للمتحاورين. تهدف الدراسة إلى التحقق من أهمية تعبيرات الوجه وكيفية تأثيرها على التواصل. الغرض من هذا البحث هو النظر في تعابير الوجه وأهميتها في عملية الإقناع خلال المقابلات السياسية حيث تأسست الدراسة على الأفكار التي يستخدمها العديد من المحاورين لتعبيرات الوجه كأداة مقنعة في التفاعل مع الآخرين للتعبير عن المشاعر والأفكار والمواقف، بالإضافة إلى تحقيق أهدافهم وإقناع الأشخاص برسائل محددة. ولتحقيق أهداف هذه الدراسة، تم استخدام نوعين من الطرق: النظرية والعملية. استلزم الطريقة النظرية شرح المفاهيم الأساسية للإقناع والتواصل غير اللفظي. من ناحية أخرى، استلزم الجانب العملي تحليل الأفلام المسجلة لمقابلتين سياسيتين مع سياسيين مختلفين. تم جمع مقاطع الفيديو من قناة اليوتيوب وتحليل المقابلات المختارة باستخدام نموذج انتقائي يعتمد على نموذج Cialdini (2001) لاستراتيجيات الإقناع، ونموذج Matsumoto (2013) لأشكال ووظائف تعبيرات الوجه العالمية، ونموذج Argyle and Dean (1965) لوظائف التواصل البصري. تظهر نتائج تحليل البيانات التي تم جمعها أن كلا المحاورين يستخدمون عادة تعبيرات الوجه كطرق مقنعة في المقابلات التلفزيونية السياسية. المحاور له تأثير على الضيف ويقنعه بالتحدث بصراحة. الضيف، من ناحية أخرى، يستخدم تعبيرات الوجه لإيصال وجهة نظره ونواياه ومشاعره إلى المحاور والجمهور. ووفقا للنتائج، فإن وظيفة البحث عن المعلومات هي أهم وظيفة للتواصل البصري، تليها وظائف السعادة والإعجاب، والتي تستخدم كطرق للإقناع. وبناء على نتائج الدراسة خلصت الدراسة إلى عدد من التوصيات والمقترحات لمزيد من البحث. During interaction, nonverbal way of communication could be used by the interlocutors. They are a crucial aspect of interlocutors' daily conversation and interaction. The study's aims to investigate the significance of facial expressions and how they affect discussions. The purpose of this research is to look into facial expressions and their significance in the persuasion process during political interviews. The study is founded on the ideas that many interlocutors utilize facial expressions as a persuasive tool in interactions with others to express emotions, thoughts, and attitudes, as well as fulfill their purposes and persuade individuals of specific messages. To achieve the aims of this study, two sorts of approaches were used: theoretical and practical. The theoretical approaches entail explaining the fundamental concepts of persuasion and nonverbal communication. The practical processes, on the other hand, entail examining recorded films of two political interviews of different politicians. The videos were collected from the YouTube channel. The selected interviews were evaluated using an eclectic model based on Cialdini's (2001) model of persuasion techniques, Matsumoto's (2013) model of universal facial expression forms and functions, and Argyle and Dean's (1965) model of eye contact functions. The results of analyzing the collected data demonstrate that both interlocutors, interviewer and interviewee, commonly employ facial expressions as persuasive methods in political TV interviews. The interviewer has an impact on the guest and persuades him to speak candidly. The guest, on the other hand, employs facial expressions to convey his point of view, intentions, and feelings to the interviewer and audience. According to the findings, the function of information seeking is the most important function of eye contact, followed by the functions of happiness and liking, which are utilized as persuasion methods. Based on the study findings, the study concluded with a number of recommendations and suggestions for further research.
Keywords: المقابلات السياسية -- الاتصال غير اللفظي -- استراتيجيات الإقناع -- التواصل البصري